Significant Association of Streptococcus bovis with Malignant Gastrointestinal Diseases - Salah Shanan; Samia A. Gumaa; Gunnar Sandström; Hadi Abd (International Journal of Microbiology)
Streptococcus bovis is a Gram-positive bacterium causing serious human infections, including endocarditis and bacteremia, and is usually associated with underlying disease. The aims of the current study were to compare prevalence of the bacterium associated with malignant and nonmalignant gastrointestinal diseases and to determine the susceptibility of the isolated strains to different antimicrobial agents. The result showed that the prevalence of S. bovis in stool specimens from patients with malignant or with nonmalignant gastrointestinal diseases was statistically significant. This result may support the idea that there is correlation between S. bovis and the malignant gastrointestinal diseases.